1980
DOI: 10.1037/0022-3514.38.1.1
|View full text |Cite
|
Sign up to set email alerts
|

Who has the final word? Sex, race, and dominance behavior.

Abstract: The effects of sex and race on a form of dominance behavior were investigated as a function of a challenger's sex and race. Dominance was defined as the number of verbal challenges against a subject's picture choice that a subject withstood. Dyads (N = 128) composed of a student and a confederate recorded individual preferences and joint decisions for the more attractive picture of 20 pairs of pictures. The number of challenges a student sustained each time a disagreement occurred regarding the more attractive… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

1990
1990
2003
2003

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 13 publications
(8 citation statements)
references
References 26 publications
1
7
0
Order By: Relevance
“…We analyzed the cases according to charac teristics (e.g., type of dispute) that we felt might conceivably be related to ethnicity or gender. We also sought to determine whether some gender differences might vary as a function of ethnicity as other researchers have reported (e.g., Adams, 1980;Hill & Crawford, 1990). Finally, we included in our study three variables that might contribute to, or perhaps explain, some of the ethnic and gender differ ences we expected to find.…”
Section: Overview Of Studymentioning
confidence: 99%
See 2 more Smart Citations
“…We analyzed the cases according to charac teristics (e.g., type of dispute) that we felt might conceivably be related to ethnicity or gender. We also sought to determine whether some gender differences might vary as a function of ethnicity as other researchers have reported (e.g., Adams, 1980;Hill & Crawford, 1990). Finally, we included in our study three variables that might contribute to, or perhaps explain, some of the ethnic and gender differ ences we expected to find.…”
Section: Overview Of Studymentioning
confidence: 99%
“…6, No. 1, January 1995 oratory studies have been conducted, there is experimental evidence of a difference in levels of dominance (Adams, 1980) and eye gaze behavior (LaFrance & Mayo, 1976) when Blacks and Whites interact in dyads. In both studies, ethnicity was also found to interact significantly with gender in influencing these behaviors.…”
Section: Related Research On Ethnicitymentioning
confidence: 99%
See 1 more Smart Citation
“…Research shows that the traits we associate with a person's gender create expectations that can profoundly influence classroom behavior and the experience of both students and teachers (7)(8)(9). We tend to expect certain behavior from females and males and consciously or subconsciously tailor many of our own responses accordingly.…”
Section: A C E D U C a T O Rmentioning
confidence: 99%
“…For example, instructors tend to recognize or call on more male students to answer questions. Research also has shown that participation in many classes is often dominated by a small group of male students who raise their hands quickly when questions are posed (5,9,10). Women were often less encouraged, or openly discouraged, from participating.…”
Section: A C E D U C a T O Rmentioning
confidence: 99%